Manejo agronómico del cultivo de chirimoya (Annona cherimola Mill) en el Ecuador - Auria Morán, Dayanna Melissa (2024)
The custard apple is a perennial plant that presents two phenological periods annually: the vegetative and reproductive periods, which makes it possible to carry out correct agronomic management of the crop, to improve the production and quality of this fruit. In this bibliographic research, the information obtained was paraphrased, summarized and analyzed. Based on the above details, it is determined that the agricultural activities involved in the agronomic management of the cherimoya crop are the following: Propagation, soil preparation, sowing, sowing density, irrigation, fertilization, pruning, weed control, pest management and diseases, manual pollination and harvest. To establish cherimoya cultivation in the defined field, it is important to select plants in good vegetative and nutritional status. Weed control in cherimoya cultivation must be done manually, with the use of scythes or machetes and not using herbicides. Cultivating cherimoya for a production of 14 tons per hectare (tn/ha) can extract: Nitrogen (N) 95 kg/ha, Phosphorus (P) 4.6 kg/ha, Potassium (P) 38 kg/ha, Calcium (Ca ) 9 kg/ha, Magnesium (Mg) 7.5 kg/ha. The cultivation of cherimoya requires the following types of pruning for its correct formation, development and fruiting: training pruning, maintenance pruning and fruiting pruning. The edaphoclimatic conditions that favor the production of the crop are: altitude (0 to 2600 meters above sea level), temperature (18 °C – 28 °C), precipitation (800 mm), luminosity (900-1200 hours per year), relative humidity ( >80%) and sandy loam soils with pH 5.5 and 6.